Point of Care Testing (POCT) to assess drug concentration in patients treated with non-vitamin K antagonist oral anticoagulants (NOACs). Issue 163 (March 2018) - Padayattil Jose, S.; Banzato, A.; Carraro, P.; Haleh, A.; Rossi, K.; Nante, G.; Denas, G.; Zoppellaro, G.; Pengo, V.
Abstract: Background: Non–vitamin K antagonist oral anticoagulants (NOACs) do not need routine laboratory monitoring but measurement of drug concentration is important in emergency conditions. Specific laboratory tests are not readily available or not implemented in every hospital. Point-of-Care Tests (POCT) may bridge this gap and be used as a bedside solution. Objectives: Feasibility of POCT to assess plasma levels of dabigatran, rivaroxaban and apixaban. Patients/methods: Activated Coagulation Time-Low Range (ACT - LR) using a portable Hemochron Signature Elite for dabigatran and prothrombin time (expressed as INR) by Coaguchek XS Pro for rivaroxaban and apixaban were obtained at trough and peak in 136 consecutive patients taking NOACs (70 on dabigatran, 45 on rivaroxaban and 20 on apixaban). Using a paired study design, drug concentrations were concurrently determined by functional specific tests. Results and conclusions: The correlation between NOACs concentration and the values obtained using the POCTs was high for dabigatran and rivaroxaban (r = 0.80 and r = 0.82, respectively) and low for apixaban (r = 0.21). ACT-LR ≤ 188 s better detected dabigatran levels ≤ 50 ng/ml, with a sensitivity of 87.5% and a specificity of 84.1%. ACT-LR values > 217 s better discriminated value of dabigatran > 200 ng/ml, with a sensitivity of 86.7% and a specificity of 81.4%. INR Coaguchek values ≤ 1.2 better identified patients with rivaroxaban values < 100 ng/ml, with sensitivity of 90%, specificity of 88.5%. This analysis was not possible for apixaban. Conclusion: In emergency situations POCT use may provide useful immediate information on dabigatran and rivaroxaban concentration. Highlights: In certain clinical situations NOACs monitoring may be of value. Peak and trough POCT and plasma concentration levels of NOACs were assessed. There was a good correlation between POCT and plasma levels of dabigatran and rivaroxaban. POCT might be a feasible tool to guide decisions certain situations in NOACs receiving patients.